EFEKTIVITAS KONSUMSI SAYUR BAYAM DAN SENAM HAMIL TERATUR DALAM MENINGKATKAN HB IBU HAMIL TM I & II DI PKM BINTUNI TELUK BINTUNI PAPUA BARAT: Effectiveness Of Regularly Spinach Consumption And Pregnancy Exercise In Increasing The Hb Of Pregnant Women TM I & II in PKM Bintuni Bintuni Bay West Papua - Pabuntak, Natalia; Muawanah, Siti; Purnomo, M.Zuhal (LPPM - STIKES Pemkab Jombang, 2024)
Women who are pregnant have a significantly higher risk of anemia due to iron deficiency. Pharmacological and non-pharmacological methods can be used to treat anemia in pregnant women. The pharmaceutical approach is to take 90 iron pills with 60 mg of iron and 50 nanograms of folic acid until the third trimester of pregnancy. Regular consumption of spinach leaves, both in the form of vegetables and juice, is effective in preventing anemia because spinach has a high iron content. Apart from consuming spinach, another factor that also contributes to an increase in Hb for pregnant women is pregnancy exercise. The purpose of this study was to analyze the differences in the consumption of spinach and regular pregnancy exercise in increasing the Hb of TM I & II pregnant women at PKM Bintuni Teluk Bintuni, West Papua. This study uses a research method that is experimental with a pre-experimental approach with the research design used is a one-group pre-test-posttest pre-experimental design. Based on the total sampling technique obtained a total sample of 28 respondents. The research results show; 1). The majority of TM I & II pregnant women, before being given the intervention, consumed spinach and regular pregnancy exercise had moderate anemia, 19 people (67.9%). 2). Most of them, after being given the intervention of consuming spinach and regular pregnancy exercise, experienced mild anemia as many as 18 people (64.3%). 3). There is a difference in the consumption of spinach and regular pregnancy exercise in increasing the Hb of TM I & II pregnant women at PKM Bintuni Teluk Bintuni, West Papua (p value 0.000 <0.05). It is hoped that health workers and health workers will introduce the concept of the importance of doing pregnancy exercise and consuming spinach to pregnant women in particular and to the general public by providing counseling to mothers once a month about the purpose and benefits of doing pregnancy exercise and consuming spinach to pregnant women. Keywords: Anemia, spinach, pregnancy exercise and pregnant women TM I and TM II